Dynamic Response Analysis of a Novel Tension-Leg Dual-Module Offshore Wind Turbine System During Both Installation and Removal Processes - Shi Liu; Xinran Guo; Yi Yang; Hongxing Wang; Shenghua Wei; Nianxin Ren; Chaohe Chen (Journal of Marine Science and Engineering)
To facilitate both the installation and the removal of floating offshore wind turbines (FOWTs), a novel tension-leg dual-module offshore wind turbine system has been proposed. This system primarily consists of a DTU 10 MW wind turbine (WT) module and a supporting tension-leg platform (TLP) module. Considering both mechanical and hydrodynamic coupling effects of the dual-module system, this study focuses on its dynamic responses during both the installation and the removal of the WT module under typical sea states. The effect of different installation vessel positions and key parameters of the clamping device on the dynamic response of the system during the WT module removal has been clarified. Based on the findings, preliminary recommendations are provided regarding the optimal positioning of the installation vessel and the optimal design parameters of the clamping device. Furthermore, an auxiliary sleeve has been proposed to facilitate the WT module removal. The results indicate that the application of the auxiliary sleeve can significantly improve the dynamic response of the system. The results of this study can serve as a reference for the design, installation, and removal of floating offshore wind turbines.